De volta para o passado histerese e estagnação na economia brasileira - Fagotti, Vinicius (2024)
This article seeks to summarize the state of the art in terms of hysteresis concepts and models, as developed from the arguments of endogeneity and heterogeneous discontinuities. It will seek to clarify the definition and the use of the term, as well as to demonstrate how to build the canonical model of hysteretic dynamics, based on non-ideal relays. The particular attributes that distinguish hysteresis from other concepts related to path dependence will also be outlined, and their basic mechanics, based on nonlinearities, selectivity and remanence, will be geometrically illustrated. The article’s final aim is to use the framework built from hysteresis to propose a new, structure-aware, interpretation regarding Brazil’s economic stagnation.